The Natural History of the Tea-Tree, with Observations on the Medical Qualities of Tea, and on the Effects of Tea-Drinking - Lettsom, John Coakley, 1744-1815 (Salt Lake City, UT : Project Gutenberg, 2021)
"The Natural History of the Tea-Tree, with Observations on the Medical Qualities of Tea" by John Coakley Lettsom is a scientific publication written in the late 18th century. The work explores the botanical aspects of the tea plant and its cultural and economic significance, particularly as it gained popularity in Europe. The text likely discusses the cultivation, preparation, and health effects of tea, contributing to its understanding as both a beverage and a medicinal herb. At the start of the text, Lettsom provides a background on the tea plant, indicating that it was cultivated in Asia, specifically China and Japan. He mentions the introduction of the tea plant to Europe and discusses its growing popularity among the public during that period. The opening also highlights various historical references and contributes to an understanding of tea's historical context, as well as detailing its cultivation processes and the challenges faced in bringing the plant to European gardens. Lettsom outlines the need for a more concise understanding of tea$1 (Bs properties, given the diverse opinions on its effects and benefits. (This is an automatically generated summary.)s
Release date is 2021-06-16
E-text prepared by Emmanuel Ackerman, John Campbell, Kobus Meyer, and the Online Distributed Proofreading Team (https://www.pgdp.net) from page images generously made available by Internet Archive (https://archive.org)
Keywords: Tea